Harnessing NKG2D CAR-T cells with radiotherapy: a novel approach for esophageal squamous cell carcinoma treatment - Tianyu Liu; Tianyu Liu; Tianyu Liu; Liyuan Fan; Liyuan Fan; Liyuan Fan; Weicheng Huang; Weicheng Huang; Pengxiang Chen; Pengxiang Chen; Yuchen Liu; Yuchen Liu; et al. (Frontiers in Immunology)
BackgroundEsophageal squamous cell carcinoma (ESCC) represents a highly aggressive malignancy with poor prognosis and limited therapeutic advancements. While chimeric antigen receptor (CAR)-T-cell therapy has revolutionized cancer treatment, its application in ESCC remains poorly explored. This study pioneers the exploration of natural killer group 2 member D (NKG2D) CAR-T cells combined with radiotherapy for treating ESCC, with the goals of establishing a novel treatment strategy and achieving superior tumor control through combined immunoradiotherapyMethodsFlow cytometry and quantitative real-time PCR (qRT-PCR) were carried out to evaluate the expression of NKG2D ligands at the cell surface protein and mRNA levels. Cell-based bioluminescence assays and enzyme-linked immunosorbent assays (ELISAs) were performed to measure the cytotoxicity and cytokine secretion of NKG2D CAR-T cells. A human ESCC subcutaneous xenograft model and a bilateral xenograft model were established. Luminex liquid suspension chip detection was utilized to verify the changes in cytokines and chemokines in the circulation and at tumor sites. Immunohistochemical analysis was conducted to assess the accumulation of T cells in vivo.ResultsNKG2D ligands are widely expressed in ESCC cell lines and can be further increased by irradiation at both the mRNA and cell surface protein levels. NKG2D CAR-T cells efficiently recognized and lysed ESCC cell lines, and irradiation enhanced the activity of NKG2D CAR-T cells targeting ESCC cells. Additionally, NKG2D CAR-T cells specifically homed to and accumulated in ESCC tumors, exerting efficient immunological activity correlated with noticeable tumor regression in a human ESCC xenograft model, with no obvious toxicity. Moreover, preconditioning with local radiotherapy accelerated the tumor shrinkage induced by NKG2D CAR-T cells, explaining by altering the tumor microenvironment (TME) and promoting the migration and infiltration of CAR-T cells into tumor sites.ConclusionsWe first clarified the therapeutic efficacy of NKG2D CAR-T cells in ESCC, as well as their enhanced effect when combined with radiotherapy, which provides a novel treatment strategy for ESCC patients.